2022
DOI: 10.1029/2021wr030964
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Role of Silt Content on the Flocculation Behavior of Clay‐Silt Mixtures

Abstract: The importance of the flocculation process in understanding depositional patterns and hence the phenomenon of sediment transport has long been acknowledged (Einstein & Krone, 1962;Gibbs, 1985;Hill et al., 2013). The added cohesion from clay sediment causes individual particles in a water column to stick together to form aggregates or flocs, which are very fragile (Guo et al., 2017;Mietta et al., 2009;Wang et al., 2018). Flocculation of natural mud has a great potential to alter flocs with sizes, densities, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…Thus, both sediment S1 and S2 are considered noncohesive. Meanwhile, previous settling experiments also showed no flocculation for suspended silt (te Slaa et al, 2013;te Slaa et al, 2015;Xu et al, 2022). Furthermore, Yao et al (2022a) discovered that silty sediment with grain size larger than 8 μm does not flocculate in freshwater (0‰ of salinity), which is consistent with our experimental phenomena.…”
Section: Casesupporting
confidence: 91%
“…Thus, both sediment S1 and S2 are considered noncohesive. Meanwhile, previous settling experiments also showed no flocculation for suspended silt (te Slaa et al, 2013;te Slaa et al, 2015;Xu et al, 2022). Furthermore, Yao et al (2022a) discovered that silty sediment with grain size larger than 8 μm does not flocculate in freshwater (0‰ of salinity), which is consistent with our experimental phenomena.…”
Section: Casesupporting
confidence: 91%
“…An experimental investigation conducted by Tran and Strom (2017) on the settling behavior of clay and silt mixtures indicated that silt particles, independent of their size, could become bound within clay flocs and that the silt content had no significant effect on floc size. However, the trapping of silt particles within flocs can have an important impact on floc density, and thus on the settling velocity which may increase by more than 50% (Tran & Strom, 2017; Xu et al., 2022). These results were confirmed by river studies (Osborn et al., 2023) and agree with Droppo and Ongley (1994), indicating that salinity is not a needed for sediments to flocculate.…”
Section: Discussionmentioning
confidence: 99%